Towards a natural classification of Dothideomycetes 7: The genera Allosoma, Austropleospora, Dangeardiella, Griggsia and Karschia (Dothideomycetes incertae sedis) - Thambugala, Kasun Madhusanka; Singtripop, Chonticha; Chunfang, Yu; Mckenzie, Eric H.c.; Liu, Zuo-Yi; Chukeatirote, Ekachai; Hyde, Kevin (Phytotaxa, 2014)
This is the seventh of a series of papers in which we report on re-examination of herbarium types of Dothideomycetes genera, incertae sedis. By examining and re-describing the generic types which are not previously illustrated or are poorly described, we attempt to propose their familial and higher placement according to the morphology based on modern taxonomic concepts. In this paper the type specimens of Allosoma, Austropleospora, Dangeardiella, Griggsia and Karschia were re-examined and are illustrated. An overview of the history and descriptions and illustrations of these genera are provided. Based on morphological similarities, Allosoma is placed in Englerulaceae, while Austropleospora and Karschia are transferred to Pleosporaceae, and Lichenotheliaceae, respectively. Dangeardiella is classified in Pleosporales, genera incertae sedis, while Griggsia is placed in Sordariomycetes, genera incertae sedis as it is not typical of any existing family of Dothideomycetes as it has unitunicate asci. Recollection, epitypifycation and multi-gene molecular analyses are needed for all type species of these genera in order to resolve their familial status. By illustrating and redescribing the type species, we expect to stimulate interest for these fungi to be recollected, sequenced and placed in a natural taxonomic framework in the Ascomycota.